Infraestructura como condición de calidad educativa en el fortalecimiento del desempeño académico estudiantil (2018)
The infrastructure as variable that boots the educational area is associated with different processes highlighting the academic performance, generating different factors that influence students’ academic performance. This reference has been a key in San Andres Island to conceive a new educational infrastructure, offering the mega schools as tool of action to solve situations of educational quality, which helps minimize the factors of low performance in school and to improve the school learning environment. The present research is an exploratory study that seeks to describe the infrastructure factors that affect students’ academic performance. From a qualitative-quantitative approach, emphasizes in the complementary paradigm. The units of analysis are represented by students, teachers’ management and guidance counselor approached by means of a descriptive - analytical design though research techniques are surveys and interviews. The principal findings show that the infrastructure dimension that influences the condition of quality and the strengthening of academic performance is the indicator of comfort and there are also other dimensions inherent to the infrastructure that also influence school performance such as: the lack of motivation on the part of teachers to use the technological dichotic materials provided by the institution and administrative policies regarding the number of students per classroom. Among the conclusions, it is of vital importance that all the agents involved in the teaching process should work in collaborative groups to plan alliance strategies to combat these factors that are damaging the student's academic performance and, in turn, the quality of education. Also, it is important that the government rethink its administrative policy in terms of the number of students per classroom when they are thinking about quality education and inclusion, because to ensure these two items it is necessary that the teacher is trained but at the same time has the necessary students that can be trapped because exceeding the number of students per classroom does not guarantee success in the process, since all students have their own worldview and learning level different and the teacher must take time to develop the class in the most permissible way for these subjects to learn more dynamically.